Green Marketing SMEs Dalam Menunjang Perekonomian Masyarakat Masyarakat Desa Bongo Dan Desa Doulan Kecamatan Bokat Kab. Buol – Sulawesi Tengah - Raflin Hinelo; Idris Yanto Niode (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
Bongo Village Doulan Village, Bokat Subdistrict, Buol Regency are categorized as remote because of their hilly and coastal geography. The majority of the population is fishermen and traditional farmers. The spread of MSMEs in the village is very large, but the level of income and welfare remains low because the products sold have no added value, are not diversified and there is no production technology intervention. This is exacerbated by the lack of skilled labor, limited means of production and narrow marketing network. This program aims to increase the income of groups of MSME business actors and craftsmen, mostly women (wives and young women) from farming and fishing families. Gender empowerment is intended so that they contribute to the improvement of the family economy. This can be achieved if the craftsmen have the knowledge and skills to produce products that are tested for quality, are attractive and reach a wide marketing network. The results of the service achievements show that 1). The achievements of the planned program are well completed; 2) The realization of the Fish-Based Home Industry Food Processing (IRT) training program for business actors in both villages with visible and measurable changes in the behavior of business actors in maximizing the production process by paying attention to environmentally friendly concepts.